Evaluation of Soil Nutrition Content of Phosphore (P) and Organic-C in Thre Locations of Intensive Rice Field in Balige District - Amri, Ulil; Syawal Harahap, Fitra; Elizabeth Mustamu, Novilda; Fadillah Zamzami, Luthfi (CV. Inara, 2024)
Evaluation of nutrient availability needs to be carried out to determine the ability of the soil to provide nutrients for plant growth, in this case the evaluation of the nutrient content of paddy fields in three locations in the Balige area, namely Huta Namora, Huta Bulu Mejan and Baruara. This is needed as information for the management of paddy fields on the provision of fertilizers in the future, both inorganic fertilizers and organic fertilizers. The purpose of this study was to evaluate the availability of soil nutrients such as organic C, total P, available P and soil pH after rice harvest. This research is a descriptive study by comparing data from the three research locations. In its implementation, 9 sample points of observation were chosen representing the location of each area. Every 3 sample points were mixed into one point of soil samples from the three research locations showing relatively the same results so that in one location there were 3 points of soil samples which were considered as replication 1, 2 and 3 replications. Thus, there were 9 soil samples for the three research locations. Based on the results of laboratory analysis shows that the nutrient content is relatively the same, namely for organic C content with low to moderate criteria, P-total nutrient content is on average between 6.55-7.52 (%) (low to moderate), for P is available between 27,241 – 28,909 with very low criteria. The pH parameter for paddy fields is relatively the same as the neutral criterion. This information becomes quite expensive information for the management of paddy fields in the future. The suggestion is to reduce the use of inorganic fertilizers and switch to the use of biological fertilizers and organic fertilizers.